Ancestral Knowledge: Taptana Cañari, A Systematic Review of the Last Four Years - Troya Vásquez, Rosa Ildaura (2024)
Objective: The research aims to analyze how this knowledge, especially Taptana, has been incorporated into educational systems during the last four years.. Theoretical Framework: This systematic review examines the integration of ancestral knowledge in education, focusing on the use of the Taptana Cañari, a mathematical instrument of the Cañari people in Ecuador. The work highlights the importance of ancestral knowledge, which encompasses cultural practices and knowledge transmitted over generations, in a context where globalization threatens its relevance. Method: The PRISMA method was used for a rigorous review and relevant studies were identified through various databases such as Scopus, SciELO, Redalyc, Dialnet, Erih Plus, Latindex and the César Vallejo University. Results and Discussion: The findings indicate that the Taptana Cañari is not only a valuable teaching resource, but also reflects an Andean worldview that can enrich mathematical learning and promote intercultural education. However, it is observed that its integration into educational curricula is limited, which poses a significant challenge for its recognition and use. Implications of the Research: The appreciation of ancestral knowledge is essential to strengthen cultural identity and promote more equitable education. Originality/Value: Generating spaces for dialogue in classrooms that integrate ancestral knowledge with modern knowledge contributes to a more sustainable future that respects cultural diversity.